Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1037/adb0000883
|View full text |Cite
|
Sign up to set email alerts
|

Review of third-wave therapies for substance use disorders in people of color and collectivist cultures: Current evidence and future directions.

Abstract: Objective: In people of color (POC) and from collectivist cultures, third-wave therapies utilizing mindfulness may be a more sensitive approach to substance use disorder (SUD) treatment, than cognitive behavioral therapy (CBT). This systematic review examined this hypothesis. Method: We searched PsycINFO, Pubmed, and MEDLINE on December 23, 2021. Articles were included if they compared efficacy of third-wave therapies to therapies with only CBT elements and reported treatment outcomes for POC/people from colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…In one of the first meta-analyses at the time, examining use of acceptance and mindfulnessbased treatments for people from diverse backgrounds related to refugee status, race, forensic, and older adults, Fuchs et al (2013) found small to large effect sizes depending on design and comparison condition, with overall small sample sizes, providing initial support but a need for future research. Other research and reviews have echoed that there is theoretical and research support for acceptance and mindfulness-based treatments for Black people and people of colour (POC), but overall there is a need for more studies with these treatments and populations (Dawson et al, 2022;Dela Cruz et al, 2022;Martinez et al, 2022b;Trefethen, 2019). MacIntyre et al (2023) reiterate the general need for new interventions to be validated to help people cope with anxiety disorders related to racism.…”
Section: Psychological Flexibility and Inflexibilitymentioning
confidence: 99%
“…In one of the first meta-analyses at the time, examining use of acceptance and mindfulnessbased treatments for people from diverse backgrounds related to refugee status, race, forensic, and older adults, Fuchs et al (2013) found small to large effect sizes depending on design and comparison condition, with overall small sample sizes, providing initial support but a need for future research. Other research and reviews have echoed that there is theoretical and research support for acceptance and mindfulness-based treatments for Black people and people of colour (POC), but overall there is a need for more studies with these treatments and populations (Dawson et al, 2022;Dela Cruz et al, 2022;Martinez et al, 2022b;Trefethen, 2019). MacIntyre et al (2023) reiterate the general need for new interventions to be validated to help people cope with anxiety disorders related to racism.…”
Section: Psychological Flexibility and Inflexibilitymentioning
confidence: 99%
“…[ 6 ] Evidence suggests that ACT might be more effective in collectivist cultures. [ 13 ] However, none of the previous studies were from the South East Asian region, representing such culture.…”
Section: Introductionmentioning
confidence: 99%